2015
DOI: 10.1590/1413-81232015207.13812014
|View full text |Cite
|
Sign up to set email alerts
|

A ótica dos conselheiros tutelares sobre a ação da rede para a garantia da proteção integral a crianças e adolescentes em situação de violência sexual

Abstract: This article aimed to ascertain the point of view of Guardianship

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
24

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 6 publications
1
17
0
24
Order By: Relevance
“…The Councils, in turn, redirect cases to other components of the sexual violence care and coping network. 21 In relation to the types of sexual violence, rape, sexual harassment, indecent assault, sexual exploitation, child pornography and others were identified. It was observed that, among the types of sexual violence, rape was the most frequent, possibly related to the fact that other types of sexual violence are not recognized as violence.…”
Section: Discussionmentioning
confidence: 99%
“…The Councils, in turn, redirect cases to other components of the sexual violence care and coping network. 21 In relation to the types of sexual violence, rape, sexual harassment, indecent assault, sexual exploitation, child pornography and others were identified. It was observed that, among the types of sexual violence, rape was the most frequent, possibly related to the fact that other types of sexual violence are not recognized as violence.…”
Section: Discussionmentioning
confidence: 99%
“…For some authors, work practices aimed at protecting children and adolescents should efficiently articulate the different sectors that make up the protection network, integrating them both in macro-structural (political) aspects and in internal aspects of services, seeking inter-institutional and interpersonal interactions 13 .…”
Section: Discussionmentioning
confidence: 99%
“…A violência sexual pode ser definida como todo ato sexual sem o consentimento da vítima ou ações de comercialização e/ou utilização da sexualidade de um individuo mediante qualquer tipo de imposição. Esse tipo de violência pode ser evidenciado em todas as faixas etárias, mas ressalta-se que atinge frequentemente crianças e adolescentes, especialmente do sexo feminino, devido às desigualdades nas relações de gênero e aos valores patriarcais da sociedade, bem como a dominação dos mais velhos sobre os mais novos (1,2).…”
Section: Introductionunclassified
“…A violência sexual infanto-juvenil pode se expressar de diferentes formas e conceitos. O abuso sexual é um tipo de violência que envolve atos ou jogos sexuais praticados por qualquer pessoa contra a criança ou adolescente, por meio de suborno, violência física ou ameaça, almejando o prazer sexual do agressor, podendo ocorrer com ou sem contato físico (2,5).…”
Section: Introductionunclassified